Why a randomized melanoma screening trial may be a good idea. (20th September 2018) - Cust, A.E.; Aitken, J.F.; Baade, P.D.; Whiteman, D.C.; Soyer, H.P.; Janda, M.
Abstract : Linked Article : Halvorsen et al. Br J Dermatol 2018; 179 :532–33.